RELATIONSHIP BETWEEN THE PERCEPTION AND SKILLS OF STUDENT BASIC SCIENCE PROCESS IN THE USE OF M-MODULE IN BASIC PHYSICS PRACTICUM - Sofia Christine Samosir; Lidia Gurning (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
This study aims to determine the relationship between perception and basic science process skills through the use of the m-module in basic physics practicum II. This research is a quantitative study using correlational design. data collection instruments used in the form of perception questionnaire instruments and observation sheets to measure students' science process skills. This study used a sample of 36 physics students at Universitas Jambi. The results of the study will be analyzed using descriptive statistics and inferential statistics. The results of this study indicate that students give a good perception of the use of the m-module in basic physics practicum II. Flat mirror material is proven from the value of the perception of 63.9% in the good category according to a predetermined range. And the basic science process skills of students are in a good category with a percentage of 50.0%. Pearson correlation results show the number 0.756 and sig 0.05 which is 0.00, this shows that there is a strong relationship between perceptions and students' science process skills in using the m-module. This means that a high perception will result in high science process skills.